Duration dependence versus unobserved heterogeneity in treatment effects: Swedish labor market training and the transition rate to employment - Katarina Richardson; Gerard J. van den Berg (Institute for Labour Market Policy Evaluation (IFAU), 2008)
The vocational employment training program is the most expensive training program in Sweden and a cornerstone of labor market policy. We analyze its causal effects on the individual transition rate from unemployment to employment by exploiting variation in the timing of treatment and outcome, dealing with selectivity on unobservables. We demonstrate the appropriateness of this approach in our con-text by studying the enrollment process. We develop a model allowing for duration dependence and unobserved heterogeneity (leading to spurious duration dependence) in the treatment effect itself, and we prove non-parametric identification. The data cover the population and include multiple unemployment spells for many individuals. The results indicate a large significantly positive effect on exit to work shortly after exiting the program. The effect at the individual level diminishes after some weeks. When taking account of the time spent in the program, the effect on the mean unemployment duration is small.
Keywords: J64; C21; C41; C14; 330; vocational training; program evaluation; duration analysis; selectivity bias; dynamic treatments; active labor market policy; identification; Arbeitsmarktpolitik; Berufsausbildung; Berufsbegleitende Ausbildung; Arbeitslosigkeit; Dauer; Berufliche Integration; Schweden